2023
DOI: 10.3390/land12112012
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics and Influencing Factors of Urban Heat Island Based on Geographically Weighted Regression Model: A Case Study of Urumqi City

Yunfei Ma,
Yusuyunjiang Mamitimin,
Bahejiayinaer Tiemuerbieke
et al.

Abstract: Rapid urbanization threatens the ecological environment and quality of life by significantly altering land use and land cover (LULC) and heat distribution. One of the most significant environmental consequences of urbanization is the urban heat island effect (UHI). This study investigated the spatiotemporal characteristics of the SUHI and its relationship with land use types from 2000 to 2020 in Urumqi City, located in an arid and semi-arid region of northwestern China. Additionally, the ordinary least squares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The UHI effect is a major concern due to its adverse effects [1,2], such as increased energy consumption [3], worsened air quality [4], and higher risks of morbidity and mortality from heat-related diseases [5]. Studies have shown a clear link between land cover types and the UHI effect [6,7]. Urban parks, as an essential component of urban blue and green infrastructure, are the most nature-like areas, with a combination of water bodies and green space patches.…”
Section: Introductionmentioning
confidence: 99%
“…The UHI effect is a major concern due to its adverse effects [1,2], such as increased energy consumption [3], worsened air quality [4], and higher risks of morbidity and mortality from heat-related diseases [5]. Studies have shown a clear link between land cover types and the UHI effect [6,7]. Urban parks, as an essential component of urban blue and green infrastructure, are the most nature-like areas, with a combination of water bodies and green space patches.…”
Section: Introductionmentioning
confidence: 99%